Resistant Palmer Amaranth Seed Production and Retention in Kansas Soybean Production - Taylor Lambert; K.B. Jeremie Kouame (Kansas Agricultural Experiment Station Research Reports, 2025)
The effective management of Palmer amaranth (Amaranthus palmeri) seedbanks is a critical challenge in Kansas soybean production. This study investigates Palmer amaranth seed production and retention at the time of soybean harvest, providing insights into the weed’s seed production in Kansas soybean fields and the potential effectiveness of harvest weed seed control tactics for its control. Data were collected from 12 counties in Kansas, where female Palmer amaranth plants were collected and seed and debris of the plant, fallen on the ground, were vacuumed. Results showed that female Palmer amaranth plants with an aboveground biomass of 0.3 and 0.4 lb produced on average 58,100 and 84,900 seeds, respectively. Moreover, approximately 97% of the seeds remained on the plant at harvest, suggesting that a Harvest Weed Seed Destruction (HWSD) strategy could be highly effective in reducing the number of Palmer amaranth viable seeds that return to the soil seedbank.
Keywords: Palmer amaranth; soybean; harvest weed seed control